Pengembangan Sistem Informasi Monitoring Checklist Maintenance untuk Efisiensi Pemeliharaan Pada Divisi General Affair - Priyadi, Angga; Fernando, Daniel; Irawan, Debi; Saelan, Athia (Journal of Information System Research (JOSH), 2026)
The General Affair (GA) Division at a telecommunications company faces problems in the maintenance checklist process, which is still carried out manually using paper and simple worksheets. This process often result in data duplication, inaccurate documentation, and delays in reporting. This research aims to develop a web-based maintenance checklist monitoring information system to support the digitalization and improve the efficiency of the facility maintenance process in the GA Division. The system development was carried out using the waterfall method through the steps of needs analysis, system design, implementation, and testing. The system was developed using the CodeIgniter 4 framework, Metronic UI interface, and MySQL as the database. Testing was conducted using the Black Box Testing method on 12 functional testing scenarios covering the main functions of the system for the roles of GA Admin and GA Officer, and all main functions of the system showed a 100% success rate according to specifications. In addition, a limited User Acceptance Test (UAT) was conducted involving GA Admin as expert judgment and GA Officers, showing that the system is easy to use, helps speed up the monitoring and reporting process, and improves the accuracy of checklist data. The research results are in the form of a web-based system that is capable of integrating the activities of various field officer roles, providing centralized data access, increasing maintenance efficiency, and supporting real-time monitoring and maintenance reporting.